2022
DOI: 10.3390/ijerph191912267
|View full text |Cite
|
Sign up to set email alerts
|

Faith-Based Community Members, Family, and COVID-19: The Role of Family Cohesion, Social Support, and Spiritual Support on Quality of Life, Depression, and COVID-19-Prevention Behaviors

Abstract: This study examined relationships between family cohesion, social support/spiritual support, and quality of life and depression among faith-based community members during the 2020 COVID-19 restrictions. Drawing upon the buffering model of social support and family cohesion as theoretical frameworks, the authors examined these factors in a survey of 551 faith-based community members between March 2020 and June 2020. Family cohesion had a direct and indirect effect (mediated by overall social support and spiritu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In many instances, the pandemic brought families closer together. A recent study found that greater family cohesion, as well as overall social support, was significantly associated with COVID-19 prevention behaviors (e.g., social distancing and masking) [ 37 ]. What is largely underemphasized in this literature is the influence that older adults have on their families in terms of encouragement and support of health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In many instances, the pandemic brought families closer together. A recent study found that greater family cohesion, as well as overall social support, was significantly associated with COVID-19 prevention behaviors (e.g., social distancing and masking) [ 37 ]. What is largely underemphasized in this literature is the influence that older adults have on their families in terms of encouragement and support of health behaviors.…”
Section: Discussionmentioning
confidence: 99%